Distress-driven impulsivity interacts with trait compulsivity in association with problematic drinking: A two-sample study - Liu, Chang; Rotaru, Kristian; Chamberlain, Samuel R.; Yücel, Murat; Grant, Jon E.; Lee, Rico S. C.; Wulandari, Teresa; Suo, Chao; Albertella, Lucy (Frontiers in Psychiatry, 2022)
Objective: Problematic drinking is highly prevalent among the general population, oftentimes leading to significant negative consequences, including physical injury, psychological problems and financial hardship. In order to design targeted prevention/early interventions for problematic drinking, it is important to understand the mechanisms that render individuals at risk for and/or maintain this behaviour. Two candidate drivers of problematic drinking are distress-driven impulsivity and trait compulsivity, with recent research suggesting these constructs may interact to enhance the risk for addictive behaviours. The current study examined whether individual differences in distress-driven impulsivity and trait compulsivity interact in relation to problematic drinking. Method: Distress-driven impulsivity (indexed by the S-UPPS-P negative urgency subscale), trait compulsivity (indexed by the CHIT scale) and problematic drinking (indexed by the BATCAP alcohol scale) were assessed in two independent samples (Sample 1, n = 117; Sample 2, n = 474) online. Bootstrapped moderation analysis was conducted to examine distress-driven impulsivity and trait compulsivity’s interaction effect on problematic drinking. Results: The interaction between distress-driven impulsivity and trait compulsivity was associated with problematic drinking in both samples. Follow-up tests revealed that, in both samples, higher trait impulsivity was associated with more problematic drinking behaviours among participants with high trait compulsivity only. Conclusions: The current findings add to the growing literature supporting an interactive relationship between impulsivity and compulsivity-related traits in relation to addictive behaviours. Both distress-driven impulsivity and compulsivity should be targeted when assessing and developing interventions for people experiencing drinking problems.